2022
DOI: 10.1097/sla.0000000000005782
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Versus Conventional Minimally Invasive Esophagectomy for Esophageal Cancer

Abstract: Objectives: To give a comprehensive review of the literature comparing perioperative outcomes and long-term survival with robotic-assisted minimally invasive esophagectomy (RAMIE) versus minimally invasive esophagectomy (MIE) for esophageal cancer. Background: Curative minimally invasive surgical treatment for esophageal cancer includes RAMIE and conventional MIE. It remains controversial whether RAMIE is comparable to MIE. Methods: This review was registered at the International Prospective Register of Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 66 publications
2
13
0
1
Order By: Relevance
“…Significant protective factors included a later year of diagnosis and higher number of resected LNs. Although not statistically significant, the histology type,43 pretreatment cM stage47 and surgical approach44–46 were included in the final model owing to their clinical relevance. The proportionality of hazards was confirmed by the Schoenfeld residual test (p=0.079).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant protective factors included a later year of diagnosis and higher number of resected LNs. Although not statistically significant, the histology type,43 pretreatment cM stage47 and surgical approach44–46 were included in the final model owing to their clinical relevance. The proportionality of hazards was confirmed by the Schoenfeld residual test (p=0.079).…”
Section: Resultsmentioning
confidence: 99%
“…Previous randomised controlled studies, including the MIRO trial44 and ROBOT trial,45 have demonstrated that both hybrid minimally invasive oesophagectomy and robotic oesophagectomy had lower complication rates than those of open surgery. Recently, an updated meta-analysis conducted by our team comparing robot-assisted versus conventional minimally invasive oesophagectomy found that robotic surgery resulted in a higher 3-year disease-free survival rate 46. Considering these results, the surgical approach was included in our predictive models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion criteria: (1) esophageal squamous cell carcinoma was con rmed by preoperative gastroscopy; (2) no distant metastasis was found in preoperative examination and postoperative pathology. Exclusion criteria: (1) previous history of cancer or malignant tumors in other parts of the body; (2) patients with severe lung diseases; (3) esophagectomy with mediastinoscopy; (4) thoracotomy or laparotomy for esophageal cancer resection; (5) Incomplete data. The study recruited 842 patients: 148 in the robotic group and 694 in the laparoscopic group.…”
Section: Patient Selectionmentioning
confidence: 99%
“…[4] With the continuous development of Da Vinci robot system, robot-assisted minimally invasive esophagectomy (RAMIE) has become another option for the minimally invasive treatment of esophageal cancer. [5] In recent years, studies on the short-term and longterm e cacy of RAMIE in the treatment of esophageal cancer have gradually attracted attention.However, as one of the most RAMIE centers in southern China, it is still important to compare the midterm survival outcomes between RAMIE and VAMIE. The aim of this study is to compare the safety, effectiveness, and mid-term survival rates of RAMIE and VAMIE using propensity score matching (PSM) analysis.…”
mentioning
confidence: 99%